Regional financial performance analysis north central timor district - Nalle, Frederic Winston; Oki, Kamilaus K.; Sanbein, Deni Silvanus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
North Central Timor Regency is one of the regencies in the border region of the Republic of Indonesia-Timor Leste. This region is still categorized as an underdeveloped region with a fairly high percentage of poverty. The most reliable source of regional revenue comes from potential regional taxes and levies. Therefore, the purpose of this study is to determine the regional financial performance when viewed from the ratio of regional financial independence, the ratio of regional financial dependence and fiscal decentralization. Some of the variables used for data analysis needs are the value of PAD, Balancing Funds and Capital Expenditures from 2001-2018 obtained from the publications of the Central Statistics Agency. The results showed thatRegional financial capacity seen from the regional financial independence of North Central Timor Regency in financing its regional needs in the context of implementing regional autonomy is still low and dependence on other regions through the central government is very high.